Pengaruh Tingkat Pengungkapan Corporate Social Responsibility (CSR) Terhadap Asimetri Informasi pada Sektor Pertambangan dan Barang Konsumsi di Indonesia dengan Variabel Kontrol Leverage dan Book-to-maket - Ineke Oktaviani; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
Researches on the disclosure of Corporate Social Responsibility (CSR) to the information asymmetry are still not many. This study aimed to identify and to prove the link between the level of CSR disclosure and information asymmetry. CSR was measured based on the GRI Index version 3.1, while the information asymmetry measured by bid-ask spread. The control variables that used in this study were leverage and book-to-market. The samples used in this study were 202 data during the period of 2008 until 2015 and tested by SPSS software version 24. The results of this study proved that Corporate Social Responsibility had a significant negative influence to information asymmetry; leverage had positive and significant influence to information asymmetry; and book-to-market had positive and significant influence to information asymmetry.